Impact of nano zinc loaded bioactive formulation on biochemical activities of Rhizoctonia Solani Kuhn and its release dynamics - Dumpapenchala Vijayreddy; Pranab Dutta; M. Gomathy; K. G. Sabarinathan; Madhusmita Mahanta; Dwipendra Thakuria; P. Bhumita; Abhinash Moirangthem; Yengkhom Linthoingambi Devi; Punabati Heisnam; Gunadhya Kumar Upamanya; Munmi Bora; et al. (Discover Sustainability)
Abstract The present study focuses on deciphering the mechanism of action of nano zinc loaded bioactive formulation (En-ZnO-NP-PGPR-BF) against the sheath blight inciting pathogen of rice, Rhizoctonia solani Kuhn. Zinc oxide nanoparticles are promising antimicrobial agents and are safer to use in field conditions as they are GRAS (Generally recognized as safe) materials. In an in vitro study, En-ZnO-NP-PGPR-BF was tested at eight concentrations (1, 5, 10, 20, 50, 100, 150, and 200 ppm) and control was kept for sterile water. The application of En-ZnO-NP-PGPR-BF demonstrated a prominent effect on the pathogen by inducing oxidative stress through the generation of reactive oxygen species (ROS) molecules, as measured by antioxidant enzymatic tests. En-ZnO-NP-PGPR-BF exhibited the best enzymatic activity at 200 ppm on superoxide dismutase (1.61 U/ml), catalase (2.97 U/ml) and malondialdehyde content (55.26 nmol/mg) compared to the control (− 0.12 U/ml, 0.04 U/ml and − 1.65 nmol/mg) respectively. When studying the effect of the optimal concentration of En-ZnO-NP-PGPR-BF on the inoculum of the pathogen, it was found that mycelial growth inhibition at 200 ppm was 98.81% and 100%, respectively. The release efficiency of the product was also significant at 200 ppm of En-ZnO-NP-PGPR-BF, with releases of 42.64%, 53.64%, 67.31%, 79.33%, and 91.50% at 2, 6, 12, 18, and 24 h, respectively. These findings suggest that En-ZnO-NP-PGPR-BF acts on the pathogen primarily by inducing oxidative stress through the generation of large amounts of ROS, facilitated by the faster release of zinc oxide nanoparticles and Iturin A molecules.